2014
DOI: 10.1371/journal.pone.0102348
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of a Gcn5-Related N-Acetyltransferase from Staphylococcus aureus

Abstract: The Gcn5-related N-acetyltransferases (GNATs) are ubiquitously expressed in nature and perform a diverse range of cellular functions through the acetylation of small molecules and protein substrates. Using activated acetyl coenzyme A as a common acetyl donor, GNATs catalyse the transfer of an acetyl group to acceptor molecules including aminoglycoside antibiotics, glucosamine-6-phosphate, histones, serotonin and spermidine. There is often only very limited sequence conservation between members of the GNAT supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
(24 reference statements)
2
7
0
Order By: Relevance
“…Our refined structures revealed that BAR is an αβ protein harboring a globular tertiary structure resembling the previously reported Gcn5-related N-acetyltransferase (GNAT) structures ( Supplementary Fig. 5) [16][17][18][19] . BAR crystalizes as a homodimer with two active sites symmetrically distributed around the dimer interface inside a large open cavity ( Fig.…”
supporting
confidence: 80%
“…Our refined structures revealed that BAR is an αβ protein harboring a globular tertiary structure resembling the previously reported Gcn5-related N-acetyltransferase (GNAT) structures ( Supplementary Fig. 5) [16][17][18][19] . BAR crystalizes as a homodimer with two active sites symmetrically distributed around the dimer interface inside a large open cavity ( Fig.…”
supporting
confidence: 80%
“…The GNAT enzyme superfamily is widespread in nature [ 26 ]. In spite of substrate diversity, GNAT superfamily members are generally characterized by a highly conserved GNAT domain (composed of 6–7 anti-parallel β-strands and 4 α-helices in the topology β1-α1-α2-β2-β3-β4-α3-β5-α4-β6-β7 [ 26 , 27 ]), and can acetylate lysine residues on histones H2B, H3, and H4. GNAT domain contains three conserved motifs in the order of D-A-B.…”
Section: Histone Acetylationmentioning
confidence: 99%
“…Motifs D preserves the stable state of these proteins. Some other members of GNAT family harbor another conserved motifs C that is located at the N-terminus of these proteins [ 27 , 28 ]. Although the structure of p300/CBP family has not yet been fully elucidated, several studies have shown that the structure and the catalytic mechanism of this group of proteins are obviously distinct from the MYST and GNAT families [ 29 ].…”
Section: Histone Acetylationmentioning
confidence: 99%
See 2 more Smart Citations